History through the prism of documentary filmmaking - Kosiuk, Oksana M. (Scholarly Publisher ICSSH, 2024)
Our methodology is based on general and special historical methods, among which the defining ones are synchronic and diachronic comparisons, analogies and comparisons (both specific modern and separate old media products). Analysis, synthesis and modeling have also become important for the interpretation and assessment of veiled realities. Since the research is based on the principles of objectivity, factuality and historicism, it was important to coordinate semiotic, structural and content analyses in order to record the origins of historical events, signs of their distortions and methods of mass consciousness manipulation. The conclusions of the research on the media coverage of the Holodomor 1932-1933 in Ukraine [2, p. 387-364] can be used for further studies of the modern history of Ukraine and revision of already traditional forms of its reconstruction, for example - chronicles.
Keywords: fact; documentary film; fiction; cinema; 366.637